2021
DOI: 10.3389/fimmu.2021.631696
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation and the Immune Response to Tuberculosis

Abstract: In 2019 10 million people developed symptomatic tuberculosis (TB) disease and 1.2 million died. In active TB the inflammatory response causes tissue destruction, which leads to both acute morbidity and mortality. Tissue destruction in TB is driven by host innate immunity and mediated via enzymes, chiefly matrix metalloproteinases (MMPs) which are secreted by leukocytes and stromal cells and degrade the extracellular matrix. Here we review the growing evidence implicating platelets in TB immunopathology. TB pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 123 publications
2
32
0
2
Order By: Relevance
“…We found that TGF-β and PF4 are representative protein signatures, confirming the result of the transcriptomic analysis and allowing us to hypothesize for these two molecules a potential role as mediators of the modulatory effects by activated platelets in vitro [21].…”
Section: Tgf-β and Pf4 Partially Mediate The Immunomodulatory Functio...supporting
confidence: 82%
See 1 more Smart Citation
“…We found that TGF-β and PF4 are representative protein signatures, confirming the result of the transcriptomic analysis and allowing us to hypothesize for these two molecules a potential role as mediators of the modulatory effects by activated platelets in vitro [21].…”
Section: Tgf-β and Pf4 Partially Mediate The Immunomodulatory Functio...supporting
confidence: 82%
“…Blood was collected in EDTA tubes centrifuged at 120 × g for 10 min at room temperature to prepare platelet‐rich plasma (PRP). The erythrocyte‐ and leukocyte‐free PRP was collected and transferred in another tube without anticoagulant for second centrifugation at 800 × g for a further 5 min [21]. Finally, the serum component was removed, and the platelets were resuspended in 2 mL of PBS 1×, pH 7.4 and used for further experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrocephalus, which is the most frequent cause of raised intracranial pressure in TBM patients, was also found to be associated with advanced stage of infection, with high morbidity and mortality (18,57). Cerebral vasculitis and inflammation both of which are regulated by platelet activation result in infarcts and are the primary cause of permanent brain tissue damage in TBM (58)(59)(60).…”
Section: Pathogenesis and Pathology Of Cns-tbmentioning
confidence: 99%
“…These findings also indicated a hypercoagulable state in TBM which is more pronounced in stage III of TBM with increased risk of thrombosis and infarction ( 207 ). Platelets are likely to be key in the inflammatory and thrombotic response to CNS-TB ( 60 ).…”
Section: Neutrophils and Strokes In Cns-tbmentioning
confidence: 99%
“…When pulmonary tuberculosis is active, elevated plasma inflammatory factors, such as C-reactive protein, increased platelet activation and the development of a hypercoagulable state, may be continued. [12][13][14] More importantly, elevated plasma inflammatory factors, such as C-reactive protein, platelet activation and the hypercoagulable state, have been found to contribute not only to an increased risk of ischemic stroke but also to a poor prognosis. [15][16][17][18] As a result, it was hypothesized that active pulmonary tuberculosis may lead to ischemic stroke through elevated plasma inflammatory factors, such as C-reactive protein, platelet activation and/or hypercoagulability, namely TBRIS.…”
Section: Introductionmentioning
confidence: 99%